Income Differences in Perceived Neighborhood Environment Characteristics among African American Women - Heather J. Adamus-Leach; Scherezade K. Mama; Daniel P. O'Connor; Rebecca E. Lee (SAGE Publishing, 2012)
Perceptions of neighborhood attributes for physical activity may be influenced by individual level income. This study examined differences in perceptions of neighborhood attributes for walking and bicycling in high and low income African American women. African American women (n = 388) aged 20-65 years completed the International Physical Activity Prevalence Study's Environmental Survey Module. Independent t -tests determined differences in perceptions of neighborhood attributes by income group. Principal component factor analysis explored differences in factor structure for survey items. Low income African American women perceived their neighborhood as being less safe with regard to crime and traffic, having fewer free recreational opportunities, and having more public transportation stops nearby. Survey items weighed differently on each factor between income groups. Household income should be taken into consideration when interpreting perceptions of neighborhood for physical activity in African American women.